2017
DOI: 10.1155/2017/8276939
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of FBXW7 Suppresses Renal Cancer Metastasis and Epithelial Mesenchymal Transition

Abstract: Background and Objective FBXW7, known as a general tumor suppressor, is commonly lowly expressed in metastatic malignancies. We aim to investigate the potential influence of FBXW7 overexpression on renal cell carcinoma (RCC) metastasis. Methods We employed quantitative real-time PCR (qRT-PCR) and Western blotting (WB) to quantify the FBXW7 expression in RCC cell lines. Upregulation of FBXW7 was performed in vitro on RCC cells using the lentivirus covering coding region FBXW7 cDNA sequence, and functional tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The present study attempted to examine how miR-27a was involved in breast cancer cell migration regulation. The expression of FBXW7 in MDA-MB-231 cells with silenced miR-27a was detected, due to the important functions of EMT regulation in cancer cells ( 20 , 21 ). The data revealed that the reduction of miR-27a increased FBXW7 expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study attempted to examine how miR-27a was involved in breast cancer cell migration regulation. The expression of FBXW7 in MDA-MB-231 cells with silenced miR-27a was detected, due to the important functions of EMT regulation in cancer cells ( 20 , 21 ). The data revealed that the reduction of miR-27a increased FBXW7 expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FBXW7 serves critical roles in regulating the metastasis of cancer cells by targeting the EMT process. In renal cancer cells, the upregulation of FBXW7 is able to effectively suppress metastasis by inhibiting EMT ( 20 ). FBXW7 is also able to regulate EMT, in part through the Ras homolog gene family member A signaling pathway in gastric cancer ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…FBW7 is directly involved in MMP-2, −9 and −13 mediated migration and invasion as a result of regulating expression of these metalloproteases (42). To determine if MMP-9 expression contributed to sT induced cell migration, initial assessments to validate whether MCV sT induces MMP-9 expression was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown MMP-9 exists in several forms; a monomeric pro form (∼92 kDa), a disulfide-bonded homodimeric (∼220 kDa) form and multiple active forms (∼67 and 82 kDa) (44, 45). The active and dimeric forms of MMP-9 play a role in the invasive and migratory phenotypes of cancer cells (42, 44, 46). MCV sT WT expression induced upregulation of dimer, pro and active forms of MMP-9, while MMP-9 protein levels upon MCV sT LSDm expression were comparable to vector control confirming that MCV sT upregulation of MMP-9 is LSD dependent.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that melanoma-associated antigen 1 interacts with FBXW7 to regulate the ubiquitin ligase-mediated turnover of Notch1 intracellular domain 1 in breast and ovarian cancer cells (42). FBXW7 upregulation also suppresses metastasis and epithelial mesenchymal transition in RCC (43). However, the biological function and underlying mechanism of FBXW7 on miRNAs remain unknown in RCC.…”
Section: Discussionmentioning
confidence: 99%